Work–family balance in the second half of life: Caregivers' decisions regarding retirement and working time reduction in Europe - Ariane Bertogg; Tiziana Nazio; Susanne Strauss (Review of Policy Research, 2021)
This article investigates how different types of informal caregiving – upward, lateral and downward – impact men's and women's decisions to retire or to reduce their working hours, and how welfare policy characteristics moderate the linkage between informal care provision and employment participation. The analyses are based on six waves from the Survey of Health, Ageing and Retirement in Europe (SHARE). We exploit the data's longitudinal structure by applying fixed-effects regression models with lagged, time-varying country characteristics. The results show that, in most cases, upward caregiving to parents is less relevant for deciding to remain in the labour market than lateral care (especially to siblings, friends and neighbours) and downward grandchild care. The welfare context moderates the impact of caregiving on labour market participation, with variation between the different types of care provided.
Keywords: 330; Europe; intergenerational relationships; kinship structure; labour market participation; unpaid care; welfare policy